2009
DOI: 10.2172/971984
|View full text |Cite
|
Sign up to set email alerts
|

Automatic differentiation of codes in nuclear engineering applications.

Abstract: The Laboratory's main facility is outside Chicago, at 9700 South Cass Avenue, Argonne, Illinois 60439. For information about Argonne and its pioneering science and technology programs, see www.anl.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Specifically, we have shown that components of the gradient can be used as additional fitting conditions in multivariate regression techniques and stochastic processesbased machine learning; the result was that surrogate response to uncertainty, which would normally require many code evaluations, could be constructed by using outputs and gradients at <10 points in the parameter space. In Figure 1, we provide an illustration from recently published research on gradient-enhanced kriging techniques: a confidence interval for order statistics of a complex simulation model (SAS subset MATWS) is correctly placed using a total of 8 model runs [11,4]. Normally, this task would require hundreds of code evaluations.…”
Section: Motivation For Automatic Differentiation Of Simulation Modelsmentioning
confidence: 99%
“…Specifically, we have shown that components of the gradient can be used as additional fitting conditions in multivariate regression techniques and stochastic processesbased machine learning; the result was that surrogate response to uncertainty, which would normally require many code evaluations, could be constructed by using outputs and gradients at <10 points in the parameter space. In Figure 1, we provide an illustration from recently published research on gradient-enhanced kriging techniques: a confidence interval for order statistics of a complex simulation model (SAS subset MATWS) is correctly placed using a total of 8 model runs [11,4]. Normally, this task would require hundreds of code evaluations.…”
Section: Motivation For Automatic Differentiation Of Simulation Modelsmentioning
confidence: 99%
“…There are several checks that need to be made [61,4,39]. First, at any level of the code, the development of the discrete adjoint model can be checked by appling the following identity…”
Section: Checking the Correctness Of The Implementationmentioning
confidence: 99%
“…Within this framework one may imagine a situation where Greeks are computed (using AD techniques) in real time to provide hedging with respect to various risk factors: interest rate, counterparty credit, correlation, model parameters etc. Due to complexity of quant libraries, AD tools and special techniques of memory management, checkpointing etc can prove extremely useful, potentially leveraging knowledge acquired during AD applications to large software packages in other areas: meteorology, computational fluid dynamics etc where such techniques were employed [43,25,45,4,39,15,8] 9.1 Block architecture for Greeks [10] presents a "Block architecture for Greeks" , using calculators and allocators. Sensitivities are computed for each block component, including root-finding and optimization routines, trees and latices.…”
Section: Calibrationmentioning
confidence: 99%
“…2 In the nuclear engineering field, the complex-step method was applied to verify first derivatives computed with other methods in MATWS, a code that "combines the point-kinetics module from the SAS4A/SASSYS computer code with a simplified representation of a reactor heatremoval system." 6 More recently, Ref. 7 implemented the complex-step method in the neutron transport equation to obtain first-order derivatives of the k-eigenvalue with respect to nuclear cross sections.…”
Section: Introductionmentioning
confidence: 99%